Strategi Penataan Kawasan Pantai Klayar Pacitan Sebagai Destinasi Pariwisata Berkelanjutan Dengan Prinsip Arsitektur Ekologis - Sri Yuliani; Wiwik Setyaningsih; Yosafat Winarto (RUAS (Review of Urbanism and Architectural Studies), 2018)
The tourism potential of Klayar Beach in Pacitan Regency is increasing along with the development of tourism programs in Indonesia which include the development of coastal areas as natural tourism destinations. The development of the coastal area for the development of the potential of local tourism based on nature requires a handling strategy that takes into account a number of considerations that are in harmony with the environment so that disaster-prone constraints can be minimized, including covering aspects of nature conservation. The strategy for developing Klayar Beach can be done through the application of the principles of Ecological Architecture. The research location in the Klayar Beach area is one of the 9 (nine) priority tourism destinations in the Regency of Pacitan. This study aims to find a regional structuring strategy with the application of the principles of ecological architecture, namely optimizing the value of regional potential and still considering the sustainability of nature. The research uses a descriptive qualitative method by conducting surveys through observation, interviews and comparing theories with relevant regulations. The results of the study are regional structuring strategies to develop the potential of Klayar Beach through structuring tourism areas in accordance with local elements and local culture as well as integrated nature conservation so that it becomes a sustainable tourism destination.